Otimização de sistema de bombeamento com energia eólica: sistema de bombeamento de São Gabriel/BA - Bruni, Carlos D´alexandria (2007)
After the Protocol of Kyoto and of the ECHO 92 - Rio de Janeiro, the attentions of the world focus to the preservation of the environment and of the maintainable use of the natural resources. People were looking for preserving environment for the future generations. Ever since, solutions are looked for the supply of energy in its more acquaintances forms and the substitution of the use of fossil fuels for the such alternative forms as: Photovoltaics, solar heat systems for water, wind , bio-diesel, etc. and in this context the Company of Engineering of the State of Bahia - Cerb changed a diesel pumping system by an wind one, It´s the first community system of this nature in Bahia. Facing problems with the model, a Cerb involved the academic segment of the Federal Center of Technological Education of Bahia Cefetba looking for a solution. This work intends to demonstrate the possibilities of optimization of the pumping communit system that supply water to approximately 50 people in the place of Romão, municipal district of São Gabriel-Ba. Technical reports were published in AGRENERGD2004-Unicamp SP and Scientific Magazine ETC,Cefetba, 2005. A simulation of the increase of energy is presented for heights of 15 and 20m, considering the eletromecanical balance from the pumping energy to the wind turbine. From the accomplished bibliographical revision, we emphasized the mechanical aspects of the engineering once in UFRN, those studies concentrate on the Department of Mechanical Engineering while, in others eletroelectronic are more emphasized. Finally, documents that we judged important were enclosed for the perfect understanding of this work